Image encryption algorithm based on Henon chaotic system - Chen Wei-bin; Zhang Xin (2009 International Conference on Image Analysis and Signal Processing, 2009)
In this paper, a new image encryption algorithm is presented based on Henon chaotic system in order to meet the requirements of secure image transfer. Shuffling the positions and changing the grey values of image pixels are combined to shuffle the relationship between the cipher-image and the original-image. First, the Arnold cat map is used to shuffle the positions of the image pixels. Second, the shuffled-image is encrypted based on Henon's chaotic system pixel by pixel. There are several parameters in this kind of chaos system and Arnold cat map. The results of several experimental, statistical analysis and key sensitivity tests show that the proposed image encryption scheme provides an efficient and secure way for image encryption. The distribution of grey values of the encrypted image exhibits a random-like behavior.